Dietary indicaxanthin from cactus pear (Opuntia ficus-indica L. Mill) fruit prevents eryptosis induced by oxysterols in a hypercholesterolaemia-relevant proportion and adhesion of human erythrocytes to endothelial cell layers. Issue 3 (14th July 2015) - Tesoriere, Luisa; Attanzio, Alessandro; Allegra, Mario; Livrea, Maria A.
Abstract : Toxic oxysterols in a hypercholesterolaemia-relevant proportion cause suicidal death of human erythrocytes or eryptosis. This process proceeds through early production of reactive oxygen species (ROS), release of prostaglandin (PGE2) and opening of PGE2-dependent Ca channels, membrane phosphatidylserine (PS) externalisation, and cell shrinkage. The present study was the first to reveal that a bioavailable phytochemical, indicaxanthin (Ind) from cactus pear fruit, in a concentration range (1·0–5·0 μM) consistent with its plasma level after a fruit meal, prevents PS externalisation and cell shrinkage in a dose-dependent manner when incubated with isolated healthy human erythrocytes exposed to an oxysterol mixture for 48 h. Dietary Ind inhibited ROS production, glutathione (GSH) depletion, PGE2 release and Ca 2+ entry. Ind alone did not modify the erythrocyte redox environment or affect other parameters. Ex vivo spiking of normal human blood with the oxysterol mixture for 48 h induced eryptosis, resulting in the production of ROS and decreased levels of GSH, which was prevented by concurrent exposure to 5 μm -Ind. The adherence of eryptotic erythrocytes to the endothelium causes vascular tissue injury. Erythrocytes isolated from blood incubated with the oxysterol mixture plus 5 μm -Ind did not adhere to endothelial cell monolayers. Eryptotic erythrocytes may contribute to thrombotic complications in hypercholesterolaemia. Our findings suggest the positive effects of diets containing Ind on erythrocytes in hypercholesterolaemic subjects.